Beban Kerja dan Konflik Kerja Sebagai Penjelas Terjadinya Stress Kerja Pelaut - Renny Hermawati; Suganjar Suganjar (Majalah Ilmiah Bahari Jogja, 2021)
The job as a seamens is vulnerable to boredom. The relatively long duration of work contracts with workloads and high work conflicts, are prone to fatigue which can lead to work stress. From a review conducted in several previous studies showed, if workload and work conflict have a positive and significant effect on work stress in several different research objects. This makes an indication that the alleged workload and work conflict will affect work stress if a study is conducted on Indonesian seamens. The Tests carried out on statistical testing models conducted on research data, with the multiple regression test approach. The results of the tests showed that work stress experienced by seamen s on board is affected by workloads and work conflicts. In this finding it can be seen that if the work stress experienced by seamens while working on board, then it is caused by the emergence of increased workloads as well as work conflicts for Indonesian seafarers who work on board.